Rural Development Program (RDP): half-year report, June 1995 - BRAC (© BRAC, 2016)
1. Introduction 2. Village organisations and credit operations 3. Employment and income generation programme 4. Special programmes 5. Social development 6. Support programmes 7. Financial statement